Why do local plant proteins not take off? : Sustainability rationalities in public catering - Kortetmäki, Teea (The International Journal of Sociology of Agriculture and Food, 2023)
This study examines the potential of local plant proteins in promoting sustainable dietary transition in public catering and, simultaneously, helping rural regions find sustainable livelihoods in the future. Environmental and health reasons call for a transition to more plant-based diets in Western countries. This poses a livelihood challenge for many rural/semi-rural regions that are currently livestock-dominated. Local plant protein crops could be a ‘win-win’ solution, both for promoting dietary transition and for supporting local rural economies – presently two conflicting objectives in regions where animal production prevails. This study is based on a development project in which local public catering actors undertook to increase the use of local plant proteins. It analyses public actors’ rationalities that explain actions and inactions for sustainability transition and the positioning of plant proteins therein. Results demonstrate how the dominant catering rationalities, and mismatches between regime and niche actor rationalities, hinder the mainstreaming of local plant proteins. The discussion reflects upon ways to overcome these barriers.